2017
DOI: 10.3748/wjg.v23.i30.5589
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Xiangsha Liujunzi granules for functional dyspepsia: A multi-center randomized double-blind placebo-controlled clinical study

Abstract: AIMTo assess the efficacy and safety of a Chinese herbal medicine (CHM), Xiangsha Liujunzi granules, in the treatment of patients with functional dyspepsia (FD).METHODSWe performed a randomized, double-blind, placebo-controlled trial with patients from three centers. Two hundred and sixteen subjects diagnosed with FD according to ROME III criteria and confirmed by upper gastrointestinal endoscopy and spleen-deficiency and Qi-stagnation syndrome were selected to receive Xiangsha Liujunzi granules or placebo for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Functional dyspepsia (FD) is a common upper gastrointestinal disorder that occurs in 11–29% of the population globally. [ 1 ] Patients with FD usually complain of chronic or recurrent epigastric pain, epigastric burning, postprandial fullness, and early satiety, which severely impair patients' quality of life. [ 2 ] In general, FD is divided into two subtypes according to the main complaints: epigastric pain syndrome, in which the patients mainly complain of epigastric pain and/or burning, and postprandial distress syndrome (PDS), in which the patients mainly complain of postprandial fullness and/or early satiety.…”
Section: Introductionmentioning
confidence: 99%
“…Functional dyspepsia (FD) is a common upper gastrointestinal disorder that occurs in 11–29% of the population globally. [ 1 ] Patients with FD usually complain of chronic or recurrent epigastric pain, epigastric burning, postprandial fullness, and early satiety, which severely impair patients' quality of life. [ 2 ] In general, FD is divided into two subtypes according to the main complaints: epigastric pain syndrome, in which the patients mainly complain of epigastric pain and/or burning, and postprandial distress syndrome (PDS), in which the patients mainly complain of postprandial fullness and/or early satiety.…”
Section: Introductionmentioning
confidence: 99%
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Literature searches identified 3782 potentially relevant titles after elimination of duplicates. After review of the abstracts, 121 full‐text publications were assessed, of which 50 studies were included in this review, involving a total of 7396 participants. As two of the studies shared the same group of patients with two aspects of results reported, so their data was abstracted as one, resulting in totally 49 trials for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…us function of gathering Qi is closely related to the whole body condition and more closely to circulation and respiratory function, as Zhang Xichun said "gathering Qi actually controls general health while remains in cheat." Like Qi deficiency, when there is insufficient of Zong Qi, we often show symptoms such as fatigue and shortness of breath, which leads to decreased activity tolerance [2,43]. With the development of modern medicine, we found that the function of Zong Qi is related to the respiratory system, circulatory system, nervous system, and even reproductive system.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%